Nanofiber composite vehicle air filter paper with gradient structure and preparation method thereof
By combining electrospinning and electrostatic spraying technology on air filter paper to form a gradient structure nanofiber composite filter paper, and strengthening the bonding strength through hot pressing composite, the problem of poor bonding fastness between nanofibers and substrates is solved, significantly improving Filtration performance and reuse efficiency achieve the effect of efficient filtering and removal of PM0.3 particles.
Patent Information
- Application Number
- CN202211285837.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2022-10-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The poor bonding fastness between nanofibers and substrates in nanofiber filters leads to low filtration efficiency and cannot be reused, limiting the practical application of nanofibers in air filter materials.
The nanofiber composite vehicle-mounted air filter paper with a gradient structure is used. The preparation method includes combining electrospinning and electrostatic spraying technology to form a multi-layer composite filter paper, and the bonding strength is enhanced by the hot pressing composite process.
It realizes a firm bond between nanofibers and substrates, maintains good dimensional stability and mechanical strength, and improves filtration performance. It performs excellently in reusing and efficient filtration of PM0.3 particles, achieving air filtering material H12 standard.
Smart Images

Figure CN115534454B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air purification, and in particular relates to a nanofiber composite vehicle-mounted air filter paper with a gradient structure and a preparation method thereof. Background Art
[0002] As an important part of the intake system, the automobile engine air filter can effectively filter out dust or sand suspended in the air to reduce the wear of valves, cylinders, pistons and other related parts, avoid serious "cylinder pulling" and "cylinder explosion" phenomena, and enable the engine to work under normal working conditions, thereby increasing the overall service time of the engine. When the engine is working normally, the air first enters the intake manifold after being filtered by the filter element, and then passes through the throttle valve and the intake pressure regulator box in turn and finally flows into the cylinder of the engine. Without the air filter installed, the unfiltered air cannot burn normally when it comes into contact with the automobile fuel, and carbon deposits are easily generated in the engine cylinder. In severe cases, it will cause the vehicle to accelerate weakly during driving and affect the exhaust emissions. In addition, due to the use of the engine air filter, the engine intake resistance is bound to increase, which not only affects the power output of the engine, but also affects the economic performance of the engine. It can be seen from this that the air filter can increase the life of the engine and ensure the stable output of power.
[0003] In the traditional electrospinning process, the diameter of the prepared nanofibers is 100-300nm, and the prepared nanofiber membranes still have the mechanical and chemical properties of the original raw materials. However, due to the coarse fiber diameter and large pore size, the interception performance of particles of various sizes in the air is low, which limits the application of high-performance nanofibers in air filtration materials.
[0004] Electrostatic spraying technology is different from traditional electrospinning processing technology. It mainly uses the effect of high-voltage electrostatic field to make the polymer solution form suspended conical droplets at the end of the nozzle, which researchers call Taylor cones. When the charge repulsion on the surface of the droplets exceeds its surface tension, the suspended droplets begin to split into numerous small droplets, referred to as "spray"; these droplets fly at high speed in the electric field accompanied by the stretching effect of the electric field force, solvent volatilization, solidification and self-assembly formation mechanism, and finally deposit on the grounded receiving device to form polymer mesh fibers. Its diameter is generally distributed between 10-30nm. The ultrafine nanofiber network formed by electrostatic spraying has the characteristics of small pore size and high porosity, but also has low strength characteristics.
[0005] In addition, most researchers today focus on the modification of nanofibers themselves, and little research has been done on the bonding strength between nanofibers and substrates. In actual applications and tests, the bonding strength between nanofibers and substrates will seriously affect their filtration performance. Especially in the self-cleaning backflush test (one of the industry standard tests for air filtration materials), poor bonding strength will significantly reduce the filtration performance of nanofiber filter materials and make them unreusable, greatly limiting the practical application of nanofibers. Summary of the invention
[0006] In response to the technical problems of poor bonding strength between nanofibers and substrates and low filtration efficiency in nanofiber filter materials, the present invention proposes a nanofiber composite vehicle air filter paper with a gradient structure and a preparation method thereof. The nanofiber composite vehicle air filter paper not only has excellent filtration performance, but also has reliable bonding between the nanofibers and the substrate, and can still maintain good dimensional stability and mechanical strength after repeated cleaning, and can maintain stable filtration of particulate matter for a long time.
[0007] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure comprises the following steps:
[0009] (1) stirring and dissolving polymer I, adhesive and curing agent in solvent I in sequence to prepare nanofiber spinning solution;
[0010] (2) stirring and dissolving triethylamine salt, polymer II, adhesive and curing agent in solvent II in sequence to prepare ultrafine nanofiber spinning solution;
[0011] (3) spinning the nanofiber spinning solution obtained in step (1) by using electrospinning technology, and spraying a layer of nanofibers on the receiving substrate as filter paper to obtain nanofiber membrane filter paper;
[0012] (4) The ultrafine nanofiber spinning solution prepared in step (2) is spun using electrostatic spray technology, and the receiving substrate is the nanofiber membrane filter paper prepared in step (3), and a layer of ultrafine nanofiber mesh is sprayed on it to obtain a multi-layer composite filter paper.
[0013] (5) The layers of the multi-layer composite filter paper obtained in step (4) are bonded together through a hot pressing composite process to obtain a nanofiber composite vehicle air filter paper.
[0014] Preferably, polymer I needs to be dried in advance at a drying temperature of 50-75° C. for at least 2 hours.
[0015] Preferably, polymer II needs to be dried in advance at a drying temperature of 50-75° C. for at least 2 hours.
[0016] In the step (1), the mass ratio of the adhesive to the polymer I is 1:(2-5), the mass ratio of the curing agent to the polymer I is 1:(10-100), and the mass ratio of the solvent I to the polymer I is (12-25):1.
[0017] In the step (2), the mass ratio of triethylamine salt to polymer II is 1:(5-8), the mass ratio of adhesive to polymer II is 1:(2-5), the mass ratio of curing agent to polymer II is 1:(10-100), and the mass ratio of solvent II to polymer II is (12-25):1.
[0018] The polymer I is polystyrene or polyacrylonitrile; the solvent I is N,N-dimethylacetamide or N,N-dimethylformamide; the polymer II is polyvinylidene fluoride or polyurethane; the solvent II is N,N-dimethylacetamide or N,N-dimethylformamide; the adhesive in step (1) or (2) is ethyl acrylate, and the curing agent is polyetheramine; the triethylamine salt is any one of triethylamine hydrochloride, triethylamine sulfate or triethylamine nitrate, or a combination of two or more thereof; preferably, the triethylamine salt is triethylamine hydrochloride.
[0019] Preferably, the curing agent in step (1) or (2) is polyether ZT-143 curing agent.
[0020] The dissolution conditions of the components in step (1) are as follows: the stirring and dissolving temperature of polymer I is 60-70°C; the stirring and dissolving temperature of the adhesive is 40-55°C; the stirring and dissolving temperature of the curing agent is 20-25°C, and the stirring time is 10-30 minutes.
[0021] The dissolution conditions of the components in step (2) are as follows: the stirring and dissolving temperature of the triethylamine salt is 60-70°C; the stirring and dissolving temperature of the polymer II is 80-120°C; the stirring and dissolving temperature of the adhesive is 40-55°C; the stirring and dissolving temperature of the curing agent is 20-25°C, and the stirring time is 10-30 minutes.
[0022] Preferably, the stirring and dissolving time of the adhesive in step (1) or step (2) is 2-4 hours.
[0023] The parameters of the electrospinning technology in step (3) are as follows: the spinning voltage of the high-voltage generator is 10-80KV, the distance from the nozzle to the receiving base fabric is 15-20cm, the nozzle diameter is 0.15-0.3cm, and the flow rate of the ejected electrospinning liquid is 0.5-1.5mL / h.
[0024] By controlling the receiving time of electrospinning, the thickness of the nanofiber membrane can be adjusted, and the receiving time can be controlled according to actual needs. Preferably, the receiving time is 5-30 minutes.
[0025] The filter paper in step (3) is cellulose filter paper; preferably, the pore size distribution of the cellulose filter paper is 75-100 μm, and the gram weight is 50-300 g / m 3 .
[0026] The parameters of the electrostatic spraying technology in step (4) are: the voltage of the high-voltage generator is 40-80KV, the distance from the spray nozzle to the receiving base cloth is 18-25cm, the diameter of the spray nozzle is 0.05-0.2cm, the flow rate of the sprayed electrospinning liquid is 0.2-1.0mL / h, and the receiving time is 5-30min.
[0027] In the hot pressing composite process of step (5), the hot pressing temperature is 60-130° C., the pressure is 0.5-2 MPa, and the hot pressing speed is 50-300 r / min.
[0028] A nanofiber composite vehicle air filter paper prepared by the above method comprises an ultrafine nanofiber web, a nanofiber membrane and a filter paper arranged in sequence, wherein the average fiber diameter of the ultrafine nanofiber web is 20-35 nm, and the average fiber diameter of the nanofiber is 200-300 nm. Preferably, the porosity of the vehicle air filter paper is 0.25-0.85 cm 3 / g
[0029] Beneficial effects of the present invention: The prepared nanofiber composite vehicle air filter paper has a gradient structure, and the fiber diameter is distributed in the range of about 20-300nm, and has the advantages of fine diameter, small pore size, high strength, good filtering effect, etc. The nanofiber composite vehicle air filter paper has a good filtering effect on PM under the industrial standard wind speed (5.33cm / s). 0.3 The initial filtration efficiency of particulate matter can reach 99.9%, reaching the H12 standard for air filtration materials. More importantly, in the self-cleaning backflush test, compared with ordinary nanofiber filter materials (the filtration efficiency drops by more than 50%), the PM0.3 filtration efficiency of the present invention can still be maintained at more than 90% after 10,000 backflush tests, demonstrating the strong composite strength between the layers of the composite filter paper and the high filtration efficiency.
[0030] The prepared gradient structure nanofiber membrane is covered on the cellulose filter paper through hot pressing and bonding. Relying on the good mechanical properties of the cellulose filter paper itself and the high surface energy of the nanofiber, the vehicle air filter paper has the characteristics of oil resistance, wear resistance, high hardness, good elasticity, low resistance, high efficiency, high filtration accuracy, and long life. It also uses a combination of electrospinning and electrostatic spraying, which saves energy, has a simple process flow, is easy to operate, and can be mass-produced, providing convenient conditions for effectively improving the engine intake quality and improving fuel efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is an electron microscope image of nanofiber composite vehicle air filter paper with gradient structure.
[0033] Figure 2 This is a physical picture of the nanofiber composite vehicle air filter paper with a gradient structure. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure comprises the following steps:
[0037] 1) Pour 1.2g of PS into different beakers and place them in an oven at 75°C for 2 hours. Then weigh 18g of (N,N-dimethylacetamide)DMAc and add it to the bottle containing the corresponding PS and stir with a magnetic stirrer. The stirring temperature is 60°C, the speed is 500r / min, and the stirring time is 4h.
[0038] 2) Add 0.4 g of ethyl acrylate adhesive to the solution obtained in step 1), place it on a magnetic stirrer and stir it at a temperature of 55° C., a speed of 350 r / min, and a stirring time of 2 h.
[0039] 3) The reaction product obtained in step 2) was placed at room temperature, 0.02 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 25° C., a stirring speed of 50 r / min, and a stirring time of 30 min.
[0040] 4) Pour 0.8 g of PVDF into different beakers and place them in an oven at 75° C. for 2 hours.
[0041] 5) Weigh 0.1g of triethylamine hydrochloride crystals into a clean glass bottle, then weigh 18g of (N,N-dimethylacetamide)DMAc and add it to the corresponding bottle and stir with a magnetic stirrer. To ensure that the triethylamine hydrochloride crystals are fully dissolved, stir at 70°C, 500r / min, and 4h.
[0042] 6) Then, the raw material of step 4) was added to the triethylamine hydrochloride / DMAc solution obtained in step 5), and the mixture was placed on a magnetic stirrer for stirring at a temperature of 80° C., a stirring speed of 300 r / min, and a stirring time of 8 h.
[0043] 7) Add 0.4 g of ethyl acrylate adhesive to the solution obtained in step 6), place it on a magnetic stirrer and stir it at a temperature of 40° C., a speed of 200 r / min, and a stirring time of 2 h.
[0044] 8) The reaction product obtained in step 7) was placed at room temperature, 0.01 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 20° C., a stirring speed of 50 r / min, and a stirring time of 10 min.
[0045] 9) The solution obtained in step 3) is spun by electrospinning technology, and the PS nanofibers are sprayed onto the irregularly arranged cellulose filter paper. The irregular cellulose filter paper is made of wood pulp by papermaking technology, and the pore size distribution is 75 μm. When the electrospinning device is working, the voltage of the high-voltage generator is 50KV; the distance from the nozzle to the receiving base cloth is 20cm; the nozzle diameter is 0.15cm; the flow rate of the electrospinning solution sprayed is 1.5mL / h; and the receiving time is 30min.
[0046] 10) The solution obtained in step 8) is spun by electrostatic spray technology, and the ultrafine PVDF nanofiber web is sprayed onto the filter paper obtained in step 9). When the electrostatic spray device is working, the voltage of the high voltage generator is 80KV; the distance from the spray nozzle to the receiving base fabric is 20cm; the diameter of the spray nozzle is 0.2cm; the flow rate of the electrostatic spinning solution sprayed is 0.5mL / h; the receiving time is 5min, and a multi-layer composite filter paper is obtained.
[0047] 11) The multi-layer composite filter paper obtained in step 10) is tightly bonded together by hot pressing, wherein the hot pressing temperature is 80° C., the hot pressing pressure is 1 MPa, and the hot pressing speed is 300 r / min to obtain a nanofiber composite vehicle air filter paper, such as Figure 2 shown.
[0048] Depend on Figure 1It can be seen that the diameter of the PS nanofiber obtained is 280nm, the average diameter of the PVDF ultrafine nanofiber web is 30nm, and the porosity of the nanofiber composite vehicle air filter paper is 0.68cm 3 / g. Then, the prepared nanofiber composite vehicle air filter paper was tested for its performance using the TSI8130A filter material test system. The filter medium was 0.3μm NaCl aerosol, the air flow rate was 32L / min, and the wind speed was 5.33cm / s. The test showed that the nanofiber composite vehicle air filter paper had a good performance on PM 0.3 The initial filtration efficiency of particulate matter can reach 99.9%, reaching the H12 standard for air filtration materials. In the self-cleaning backflush test, after 10,000 backflush tests, the PM 0.3 The filtration efficiency is 91%.
[0049] Example 2
[0050] A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure comprises the following steps:
[0051] 1) Pour 0.9g of PAN into different beakers and place them in an oven at 50°C for 2 hours. Then weigh 18.8g of (N,N-dimethylacetamide)DMAc and add it to the bottle containing the corresponding PAN and stir with a magnetic stirrer. The stirring temperature is 60°C, the speed is 500r / min, and the stirring time is 4h.
[0052] 2) Add 0.4 g of ethyl acrylate adhesive to the solution obtained in step 1), place it on a magnetic stirrer and stir it at a temperature of 55° C., a stirring speed of 2000 r / min, and a stirring time of 4 h.
[0053] 3) The reaction product obtained in step 2) was placed at room temperature, 0.02 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 20° C., a stirring speed of 100 r / min, and a stirring time of 20 min.
[0054] 4) Pour 0.9 g of PU into different beakers and place them in an oven at 60° C. for 2 hours.
[0055] 5) Weigh 0.15g of triethylamine hydrochloride crystals into a clean glass bottle, then weigh 18.8g of (N,N-dimethylacetamide)DMAc and add it to the corresponding bottle and stir with a magnetic stirrer. To ensure that the triethylamine hydrochloride crystals are fully dissolved, the stirring temperature is 70℃, the speed is 600r / min, and the stirring time is 4h.
[0056] 6) Then, the raw material of step 4) was added to the obtained triethylamine hydrochloride / DMAc solution, and the solution was placed on a magnetic stirrer for stirring at a temperature of 90° C., a stirring speed of 400 r / min, and a stirring time of 9 h.
[0057] 7) Add 0.3 g of ethyl acrylate adhesive to the solution obtained in step 6), place it on a magnetic stirrer and stir it at a temperature of 55° C., a speed of 250 r / min, and a stirring time of 4 h.
[0058] 8) The reaction product obtained in step 7) was placed at room temperature, 0.05 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 25° C., a stirring speed of 100 r / min, and a stirring time of 10 min.
[0059] 9) The solution obtained in step 3) is spun by electrospinning technology, and the PAN nanofibers are sprayed onto the irregularly arranged cellulose filter paper. The irregular cellulose filter paper is made of wood pulp by papermaking technology, and has a pore size of 75 μm. When the electrospinning device is working, the voltage of the high-voltage generator is 60KV; the distance from the nozzle to the receiving base fabric is 16cm; the nozzle diameter is 0.2cm; the flow rate of the electrospinning solution sprayed is 0.6mL / h; and the receiving time is 10min.
[0060] 10) The solution obtained in step 8) is spun by electrostatic spraying technology, and the ultrafine PU nanofiber web is sprayed onto the filter paper obtained in step 9). When the electrostatic spray device is working, the voltage of the high-voltage generator is 50KV; the distance from the spray nozzle to the receiving base fabric is 18cm; the diameter of the spray nozzle is 0.2cm; the flow rate of the electrostatic spinning solution sprayed is 0.8mL / h; the receiving time is 15min, and a multi-layer composite filter paper is obtained.
[0061] 11) The multi-layer composite filter paper obtained in step 10) is tightly bonded together by hot pressing, the hot pressing temperature is 80° C., the hot pressing pressure is 0.5 MPa, and the hot pressing speed is 100 r / min to obtain a nanofiber composite vehicle air filter paper.
[0062] The average diameter of the PAN nanofibers was 202nm, the average diameter of the PU ultrafine nanofiber web was 21nm, and the porosity of the nanofiber composite vehicle air filter paper was 0.52cm 3 / g.
[0063] Example 3
[0064] A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure comprises the following steps:
[0065] 1) Pour 0.9g of PS into different beakers and place them in an oven at 60°C for 2 hours. Then weigh 18.8g of (N,N-dimethylacetamide)DMAc and add it to the bottle containing the corresponding PS and stir with a magnetic stirrer. The stirring temperature is 70°C, the speed is 500r / min, and the stirring time is 4h.
[0066] 2) Add 0.4 g of ethyl acrylate adhesive to the solution obtained in step 1), place it on a magnetic stirrer and stir it at a temperature of 50° C., a stirring speed of 300 r / min, and a stirring time of 4 h.
[0067] 3) The reaction product obtained in step 2) was placed at room temperature, 0.05 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 22° C., a stirring speed of 60 r / min, and a stirring time of 10 min.
[0068] 4) Pour 0.9 g of PVDF into different beakers and place them in an oven at 55° C. for 2 hours.
[0069] 5) Weigh 0.25g of triethylamine hydrochloride crystals into a clean glass bottle, then weigh 18.8g of (N,N-dimethylacetamide)DMAc and add it to the corresponding bottle and stir with a magnetic stirrer. To ensure that the triethylamine hydrochloride crystals are fully dissolved, stir at 70°C, 500r / min, and 4h.
[0070] 6) Then, the raw material of step 4) was added to the obtained triethylamine hydrochloride / DMAc solution, and placed on a magnetic stirrer for stirring at a temperature of 100° C., a stirring speed of 400 r / min, and a stirring time of 10 h.
[0071] 7) Add 0.4 g of ethyl acrylate adhesive to the solution obtained in step 6), place it on a magnetic stirrer and stir it at a temperature of 55° C., a speed of 300 r / min, and a stirring time of 4 h.
[0072] 8) The reaction product obtained in step 7) was placed at room temperature, 0.02 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 20° C., a stirring speed of 100 r / min, and a stirring time of 10 min.
[0073] 9) The solution obtained in step 3) is spun by electrospinning technology, and the PS nanofibers are sprayed onto the irregularly arranged cellulose filter paper. The irregular cellulose filter paper is made of wood pulp by papermaking technology, and the pore size distribution is 100 μm. When the electrospinning device is working, the voltage of the high-voltage generator is 50KV; the distance from the nozzle to the receiving base cloth is 16cm; the nozzle diameter is 0.3cm; the flow rate of the electrospinning solution sprayed is 0.8mL / h; and the receiving time is 10min.
[0074] 10) The solution obtained in step 8) is spun by electrostatic spraying technology, and the ultrafine PVDF nanofiber web is sprayed onto the nanofiber layer obtained in step 9). When the electrostatic spray device is working, the voltage of the high voltage generator is 60KV; the distance from the spray nozzle to the receiving base fabric is 16cm; the diameter of the spray nozzle is 0.1cm; the flow rate of the electrostatic spinning solution sprayed is 0.5mL / h; the receiving time is 10min, and a multi-layer composite filter paper is obtained.
[0075] 11) The multi-layer composite filter paper obtained in step 10) is tightly bonded together by hot pressing. The hot pressing temperature is 70° C., the hot pressing pressure is 2 MPa, and the hot pressing speed is 100 r / min, to obtain a nanofiber composite vehicle air filter paper.
[0076] After testing, the diameter of the PS nanofiber obtained was 200-300nm, the diameter distribution of the PVDF ultrafine nanofiber network was 20-35nm, and the porosity of the nanofiber composite vehicle air filter paper was 0.61cm 3 / g.
[0077] Example 4
[0078] A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure comprises the following steps:
[0079] 1) Pour 0.9 g of PS into different beakers and place them in an oven at 60°C for 3 hours. Then weigh 18.8 g of (N,N-dimethylacetamide)DMAc and add it to the bottle containing the corresponding PS and stir with a magnetic stirrer. The stirring temperature is 70°C, the speed is 500 r / min, and the stirring time is 4 hours.
[0080] 2) Add 0.3 g of ethyl acrylate adhesive to the solution obtained in step 1), place it on a magnetic stirrer and stir it at a temperature of 45° C., a speed of 350 r / min, and a stirring time of 4 h.
[0081] 3) The reaction product obtained in step 2) was placed at room temperature, 0.03 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 20° C., a stirring speed of 40 r / min, and a stirring time of 10 min.
[0082] 4) Pour 0.9 g of PU into different beakers and place them in an oven at 75° C. for 2 hours.
[0083] 5) Weigh 0.2g of triethylamine hydrochloride crystals into a clean glass bottle, then weigh 19.2g of (N,N-dimethylacetamide)DMAc and add it to the corresponding bottle and stir with a magnetic stirrer. To ensure that the triethylamine hydrochloride crystals are fully dissolved, stir at 60°C, 600r / min, and 4h.
[0084] 6) Then, the raw material of step 4) was added to the obtained triethylamine hydrochloride / DMAc solution, and the solution was placed on a magnetic stirrer for stirring at a temperature of 80° C., a stirring speed of 500 r / min, and a stirring time of 10 h.
[0085] 7) Add 0.3 g of ethyl acrylate adhesive to the solution obtained in step 6), place it on a magnetic stirrer and stir it at a temperature of 45° C., a speed of 200 r / min, and a stirring time of 4 h.
[0086] 8) The reaction product obtained in step 7) was placed at room temperature, 0.01 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 20° C., a stirring speed of 50 r / min, and a stirring time of 10 min.
[0087] 9) The reaction product obtained in step 3) is used to spray PS nanofibers onto irregularly arranged cellulose filter paper by electrospinning technology. The irregular cellulose filter paper is made of wood pulp by papermaking technology, and the pore size distribution is 75 μm. When the electrospinning device is working, the voltage of the high-voltage generator is 40KV; the distance from the nozzle to the receiving base fabric is 16cm; the nozzle diameter is 0.5cm; the flow rate of the electrospinning liquid sprayed is 0.8mL / h; and the receiving time is 10min.
[0088] 10) The reaction product obtained in step 8) is sprayed onto the irregularly arranged cellulose filter paper in step 9) by using electrostatic spray technology. When the electrostatic spray device is working, the voltage of the high-voltage generator is 60KV; the distance from the spray nozzle to the receiving base fabric is 20cm; the diameter of the spray nozzle is 0.2cm; the flow rate of the electrostatic spinning solution sprayed is 0.5mL / h; the receiving time is 15min, and a multi-layer composite filter paper is obtained.
[0089] 11) The multi-layer composite filter paper obtained in step 10) is tightly bonded together by hot pressing, the hot pressing temperature is 60° C., the hot pressing pressure is 1 MPa, and the hot pressing speed is 50 r / min to obtain a nanofiber composite vehicle air filter paper.
[0090] After testing, the diameter of the PS nanofibers obtained was 200-300nm, the diameter distribution of the PU ultrafine nanofiber network was 20-35nm, and the porosity of the nanofiber composite vehicle air filter paper was 0.71cm 3 / g.
[0091] Example 5
[0092] A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure comprises the following steps:
[0093] 1) Pour 1g of PAN into different beakers and place them in an oven at 50°C for 5 hours. Then weigh 25g of (N,N-dimethylformamide)DMF and add it to the bottle containing the corresponding PAN and stir with a magnetic stirrer. The stirring temperature is 65°C, the speed is 500r / min, and the stirring time is 4h.
[0094] 2) Add 0.2 g of ethyl acrylate adhesive to the solution obtained in step 1), place it on a magnetic stirrer and stir it at a temperature of 40° C., a stirring speed of 2000 r / min, and a stirring time of 2 h.
[0095] 3) The reaction product obtained in step 2) was placed at room temperature, 0.01 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 23° C., a stirring speed of 100 r / min, and a stirring time of 20 min.
[0096] 4) Pour 1 g of PU into different beakers and place them in an oven at 60°C for 4 hours.
[0097] 5) Weigh 0.2g of triethylamine sulfate crystals into a clean glass bottle, then weigh 25g of (N,N-dimethylacetamide) DMAc and add it to the corresponding bottle and stir with a magnetic stirrer. To ensure that the triethylamine hydrochloride crystals are fully dissolved, the stirring temperature is 65℃, the speed is 600r / min, and the stirring time is 4h.
[0098] 6) Then, the raw material of step 4) was added to the obtained triethylamine hydrochloride / DMAc solution, and the solution was placed on a magnetic stirrer for stirring at a temperature of 120° C., a stirring speed of 400 r / min, and a stirring time of 6 h.
[0099] 7) Add 0.2 g of ethyl acrylate adhesive to the solution obtained in step 6), place it on a magnetic stirrer and stir it at a temperature of 45° C., a speed of 250 r / min, and a stirring time of 3 h.
[0100] 8) The reaction product obtained in step 7) was placed at room temperature, 0.01 g of polyether ZT-143 curing agent was added, and the mixture was placed on a magnetic stirrer for stirring at a temperature of 25° C., a stirring speed of 100 r / min, and a stirring time of 30 min.
[0101] 9) The solution obtained in step 3) is spun by electrospinning technology, and the PAN nanofibers are sprayed onto the irregularly arranged cellulose filter paper. The irregular cellulose filter paper is made of wood pulp by papermaking technology, and has a pore size of 75 μm. When the electrospinning device is working, the voltage of the high-voltage generator is 10KV; the distance from the nozzle to the receiving base fabric is 15cm; the nozzle diameter is 0.15cm; the flow rate of the electrospinning solution sprayed is 0.5mL / h; and the receiving time is 30min.
[0102] 10) The solution obtained in step 8) is spun by electrostatic spraying technology, and the ultrafine PU nanofiber web is sprayed onto the filter paper obtained in step 9). When the electrostatic spray device is working, the voltage of the high-voltage generator is 40KV; the distance from the spray nozzle to the receiving base fabric is 25cm; the diameter of the spray nozzle is 0.05cm; the flow rate of the electrostatic spinning solution sprayed is 0.1mL / h; the receiving time is 20min, and a multi-layer composite filter paper is obtained.
[0103] 11) The multi-layer composite filter paper obtained in step 10) is tightly bonded together by hot pressing, the hot pressing temperature is 130° C., the hot pressing pressure is 0.1 MPa, and the hot pressing speed is 50 r / min, to obtain a nanofiber composite vehicle air filter paper.
[0104] The average diameter of the PAN nanofibers was 290nm, the average diameter of the PU ultrafine nanofiber web was 34nm, and the porosity of the nanofiber composite vehicle air filter paper was 0.26cm 3 / g.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanofiber composite vehicle air filter paper with a gradient structure, characterized in that: The following steps are involved: (1) stirring and dissolving polymer I, adhesive and curing agent into solvent I in sequence to prepare nanofiber spinning solution; (2) stirring and dissolving triethylamine salt, polymer II, adhesive and curing agent in solvent II in sequence to prepare ultrafine nanofiber spinning solution; (3) spinning the nanofiber spinning solution obtained in step (1) by using electrospinning technology, spraying a layer of nanofiber membrane on the filter paper, and obtaining nanofiber membrane filter paper; (4) The ultrafine nanofiber spinning solution prepared in step (2) is spun using electrostatic spraying technology, and a layer of ultrafine nanofiber mesh is sprayed on the nanofiber membrane filter paper prepared in step (3) to prepare a multi-layer composite filter paper. (5) bonding the layers of the multi-layer composite filter paper obtained in step (4) together through a hot pressing composite process to obtain a nanofiber composite vehicle air filter paper; In the step (1), the mass ratio of the adhesive to the polymer I is 1:(2-5), the mass ratio of the curing agent to the polymer I is 1:(10-100), and the mass ratio of the solvent I to the polymer I is (12-25):1; In the step (2), the mass ratio of triethylamine salt to polymer II is 1:(5-8), the mass ratio of adhesive to polymer II is 1:(2-5), the mass ratio of curing agent to polymer II is 1:(10-100), and the mass ratio of solvent II to polymer II is (12-25):1; The polymer I is polystyrene or polyacrylonitrile; the solvent I is N,N-dimethylacetamide or N,N-dimethylformamide; the polymer II is polyvinylidene fluoride or polyurethane; the solvent II is N,N-dimethylacetamide or N,N-dimethylformamide; the adhesive in step (1) or (2) is ethyl acrylate, and the curing agent is polyetheramine; the triethylamine salt is any one of triethylamine hydrochloride, triethylamine sulfate or triethylamine nitrate, or a combination of two or more thereof; In the hot pressing composite process of step (5), the hot pressing temperature is 60-130° C., the hot pressing pressure is 0.5-2 MPa, and the hot pressing speed is 50-300 r / min.
2. The method for preparing the nanofiber composite vehicle air filter paper with a gradient structure according to claim 1, characterized in that: The stirring and dissolving conditions of the components in step (1) are as follows: the stirring and dissolving temperature of polymer I is 60-70°C; the stirring and dissolving temperature of the adhesive is 40-55°C; the stirring and dissolving temperature of the curing agent is 20-25°C, and the stirring time is 10-30 minutes.
3. The method for preparing the nanofiber composite vehicle air filter paper with a gradient structure according to claim 2, characterized in that: The stirring and dissolving conditions of the components in step (2) are as follows: the stirring and dissolving temperature of the triethylamine salt is 60-70°C; the stirring and dissolving temperature of the polymer II is 80-120°C; the stirring and dissolving temperature of the adhesive is 40-55°C; the stirring and dissolving temperature of the curing agent is 20-25°C, and the stirring time is 10-30 minutes.
4. The method for preparing the nanofiber composite vehicle air filter paper with a gradient structure according to claim 3, characterized in that: The parameters of the electrospinning technology in step (3) are: the spinning voltage of the high-voltage generator is 10-80 KV, the distance from the nozzle to the receiving base fabric is 15-20 cm, the nozzle diameter is 0.15-0.3 cm, the flow rate of the electrospinning liquid sprayed is 0.5-1.5 mL / h, and the receiving time is 5-30 min; the filter paper is cellulose filter paper.
5. The method for preparing the nanofiber composite vehicle air filter paper with gradient structure according to claim 4, characterized in that: The parameters of the electrostatic spraying technology in step (4) are: the voltage of the high-voltage generator is 40-80 KV, the distance from the spray nozzle to the receiving base fabric is 18-25 cm, the diameter of the spray nozzle is 0.05-0.2 cm, the flow rate of the electrostatic spinning solution sprayed is 0.2-1.0 mL / h, and the receiving time is 5-30 min.
6. The nanofiber composite vehicle air filter paper with gradient structure prepared by the method according to any one of claims 1 to 5, characterized in that: The invention comprises an ultrafine nanofiber net, a nanofiber membrane and filter paper which are arranged in sequence. The average diameter of the fibers in the ultrafine nanofiber net is 20-35nm, and the average diameter of the fibers in the nanofiber membrane is 200-300nm.
Citation Information
Cited By
Polyurethane composite air filter paper and preparation method thereof
CN117026685A
Combined type high-precision low-flow-resistance filter with replaceable core
CN121139087A
Preparation method of industrial gas composite filter material
CN122381399A
